Viability Of Robusta Coffee (Coffea Canephora) Seeds At Several Concentrations And Duration Of Giberelin (Ga3) - Lilis Karlina; Dede Suhendra; Warnita (Jurusan Budidaya Perkebunan, 2023)
Robusta coffee (Coffea canephora) germination takes a long time because robusta coffee beans have a hard seed coat that makes it difficult for water and oxygen to penetrate, causing the germination process to be hampered. The purpose of this study is to determine the gibberellin concentration, and the proper soaking time in the germination of robusta coffee seeds and to obtain the best interaction between gibberellin concentration and soaking time on the viability of coffee seeds that have been peeled. The research was conducted at the Dharmasraya Campus III Seed Technology Laboratory from July to September 2022. This study was a two-factorial experiment in a completely randomized design (CRD). The first factor was the concentration of gibberellins which had four levels: 0, 100, 200, and 300 ppm, the second factor was soaking time which had 3 levels: 8, 16, and 24 hours. The results showed that the treatment with gibberellin of 300 ppm significantly increased seed germination, plumule, radicle elongation, and vigor index on robusta coffee seeds. And, the best soaking time of 24 hours, the long soaking treatment had a significant effect on the germination power of robusta coffee seeds. With the best treatment, a gibberellin concentration of 300 ppm and 24 hours, the interaction between gibberellins concentration and soaking time can increase the germination power of robusta coffee seeds.